Methodological aspects of ecosystem service valuation at the national level - David Vačkář; Ioanna Grammatikopoulou; Jan Daněk; Eliška Lorencová (One Ecosystem, 2018)
Ecosystem service valuations focusing on the assessment of ecosystem service values in space and time have recently been receiving considerable attention. Ecosystem service valuation data are critical for developing national ecosystem accounts and for assessment of costs and benefits associated with national strategies and plans. In this article, we discuss selected methodological aspects of ecosystem service valuation at the national level for the Czech Republic. We present a classification of ecosystems based on CORINE Land Cover and Consolidated Layer of Ecosystems of the Czech Republic. The focal point of our article is a systematic review of ecosystem service values. A systematic review requires a standardised protocol for incorporation of valuation studies. To illustrate the proposed methodology, we conducted a search of ecosystem service valuation studies at the European level. While there is a significant number of ecosystem service valuation studies, the number of studies which could be used for an effective value transfer is limited. We discuss the limitations of the value transfer approach and suggest further steps for improving the scientific basis for national level valuations.